Sequelae and Quality of Life in Patients Living at Home 1 Year After a Stroke Managed in Stroke Units - Broussy, Sophie; Saillour-Glenisson, Florence; García-Lorenzo, B.; Rouanet, Francois; Lesaine, Emilie; Maugeais, Melanie; Aly, Florence; Glize, Bertrand; Salamon, Roger; Sibon, Igor (Frontiers in Neurology, 2019)
Introduction Knowledge about residual deficiencies and their consequences on daily life activities among stroke patients living at home one-year after the initial event managed in stroke units is poor. This multi-dimensional study assessed the types of deficiencies, their frequency and the consequences that the specific stroke had upon the daily life of patients. Methods A cross-sectional survey, assessing, using standardized scales, one year post-stroke disabilities, limitations of activities, participation and quality of life, was carried out by telephone interview and by mail in a sample of stroke patients who returned home after having been initially managed in a stroke unit. Results A total of 161 patients were included (142 able to answer the interview on their own; 19 needing a care-giver). Amongst a sub-group of the patients interviewed, 55.4% (95% Confidence Interval [47.1-63.7]) complained about pain and 60.0% (95% CI [51.4-68.6]) complained of fatigue; about 25% presented neuropsychological or neuropsychiatric disability. Whilst 87.3% (95% CI [81.7-92.9]) were independent for daily life activities, participation in every domains and quality of life scores, mainly in daily activity, pain and anxiety subscales, were low. Conclusion Despite a good one-year post-stroke functional outcome, non-motor disabling symptoms are frequent amongst patients returned home and able to be interviewed, contributing to a low level of participation and a poor quality of life. Rehabilitation strategies focused on participation should be developed to break the vicious circle of social isolation and improve quality of life.